Do destacamento de enunciados à produção de discursos sobre língua: as dimensões de uma polêmica midiática - Silva, Evilásio do Nascimento (2020)
This paper analyzes aspects related to the functioning of a media controversy triggered by the publication of a didactic book distributed by the Ministry of Education. This paper is situated in the scope of French discourse analysis, and it follows the theoretical-methodological framework presented by Dominique Maingueneau. This study allows us to trace the discursive clash that is known at the moment when the issues involving the language are at the center of a public debate. The research corpus consists of texts that materialize two main discourses represented, on one hand, by the group of those who claim that the didactic book openly defends the Portuguese error and, on other hand, by the group of those who consider that the book was misinterpreted, that the standards were based on some phrases taken from their original context. The results point to the way in which each discourse interprets its Other in the discursive space, in other words, it is how each of them translates its opponent by investing in linguistic and discursive mechanisms, especially in the integration/disqualification of the opponent. About these strategies, we believe that they are the reflection of the incompatibility between two semantic universes, which, in this case, leaves marks on the discursive surface. In general, it is interesting to deepen the discussion on the functioning of the discourses approached, especially those concerning the construction of discursive identities. In the theoretical-methodological context, the investigation undertaken confirms that the parameters that can be taken into account in the characterization of the controversy are diverse, and an increasingly integrative analysis, sensitive to the multiple discursive plans that cross the controversial, is essential.